(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2018)
For the People: A Documentary History of the Struggle for Peace and Justice in the United States, edited by Charles F. Howlettt and Robbie Lieberman, Charlotte, NC, Information Age Publishing, 2009, 351 pp., US 39.09 (paperback), US 73.09 (hardcover), ISBN 978-1-60752-305-5 (paperback).